L'âge de la responsabilité pénale - Choquette, Marie (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
The jurisdiction of the youth court depends on the age of the person who appears before it. Since the federal Young Offenders Act came into effect, the minimum limit has been established at twelve years of age. Consequently, sections 12 and 13 of the Criminal Code have been repealed. In the Province of Quebec, before Bill 60 came into effect, the lower age limit was fourteen years. Since the bill came into force, however, the Youth ProtectionAct has become essentially a law of protection and all federal offences must be treated in accordance with the Young Offenders Act. Many reasons persuaded the legislator to lower the minimum age from fourteen to twelve years of age, but it seems that the most convincing was a decline of the age of juvenile criminality. Finally, the Young Offenders ACt establishes the maximum age limit at eighteen years of age and standardizes that age accross Canada from April 1, 1985. Reasons of uniformity, equity and constitutionality have influenced the legislator in setting the upper age limit at eighteen years of age.